Data Standards: At the Intersection of Sites, Clinical Research Networks, and Standards Development Initiatives - McCourt, Brian; Harrington, Robert A.; Fox, Kathleen; Hamilton, Carol Dukes; Booher, Kimberly; Hammond, William E.; Walden, Anita; Nahm, Meredith (Drug information journal, 2007)
Interactions between the health care and clinical research communities are currently inefficient. The present environment forces unnecessary redundancy, from the capture of patient data in the clinician-patient encounter to multiple uses of thai data. Clinical research operations must become more integrated with health care processes to improve efficiencies in both patient care and research. Achieving a single instance of data capture to serve the combined needs of both environments should facilitate translation of knowledge from research into better patient care. A critical first step in achieving true interoperability is to develop formal data standards that are then adopted by the larger health care and research communities. The rewards of interoperability include streamlined subject screening and enrollment procedures, improved reporting, merging and subsequent analysis of clinical data sets, and expansion of knowledge made possible by leveraging research data and results from other domains in the health care community—all of which would increase the quality of patient care. The aggregation of data across multiple sites and the subsequent reuse of that data do face challenges, particularly in ensuring patient privacy; however, these can be overcome by technological innovation and consensus-building among stakeholders.